Improvement of adynamic bone disease after renal transplantation - Abdallah,K.A. (2006)
Low bone remodeling and relatively low serum parathyroid hormone (PTH) levels characterize adynamic bone disease (ABD). The impact of renal transplantation (RT) on the course of ABD is unknown. We studied prospectively 13 patients with biopsy-proven ABD after RT. Bone histomorphometry and bone mineral density (BMD) measurements were performed in the 1st and 12th months after RT. Serum PTH, 25-hydroxyvitamin D, 1,25-dihydroxyvitamin D, and osteocalcin were measured regularly throughout the study. Serum PTH levels were slightly elevated at transplantation, normalized at the end of the third month and remained stable thereafter. Bone biopsies performed in the first month after RT revealed low bone turnover in all patients, with positive bone aluminum staining in 5. In the 12th month, second biopsies were performed on 12 patients. Bone histomorphometric dynamic parameters improved in 9 and were completely normalized in 6, whereas no bone mineralization was detected in 3 of these 12 patients. At 12 months post-RT, no bone aluminum was detected in any patient. We also found a decrease in lumbar BMD and an increase in femoral BMD. Patients suffering from ABD, even those with a reduction in PTH levels, may present partial or complete recovery of bone turnover after successful renal transplantation. However, it is not possible to positively identify the mechanisms responsible for the improvement. Identifying these mechanisms should lead to a better understanding of the physiopathology of ABD and to the development of more effective treatments.